2011
DOI: 10.1111/j.1365-2893.2011.01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon alfa‐2b plus weight‐based ribavirin for 24 weeks in patients with chronic hepatitis C virus genotype 1 with low viral load who achieve rapid viral response

Abstract: SUMMARY. In chronic hepatitis C (CHC), treatment duration may be individualized according to time to first undetectable hepatitis C virus (HCV) RNA, with patients who attain undetectable HCV RNA early in treatment being candidates for shorter regimens. The aim of this study was to determine the relapse rate in patients with CHC genotype (G) 1 infection and low baseline viral load who achieved undetectable HCV RNA by week 4 [rapid virologic response (RVR)] when treated for 24 weeks. This was an open-label, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(36 reference statements)
0
4
0
2
Order By: Relevance
“…Treatment with pegylated IFN, with or without ribavirin, results in remission rates of 75% in patients with MZL 114 and mixed cryoglobulinemia. 115 The 5-year PFS and OS rates for patients treated with upfront antiviral therapy were 78% and 92%, respectively, and anti-HCV therapy at any time was independently associated with better OS. In addition, the outcome seems to be significantly better when pegylated IFN is used.…”
Section: Local Treatmentsmentioning
confidence: 89%
See 1 more Smart Citation
“…Treatment with pegylated IFN, with or without ribavirin, results in remission rates of 75% in patients with MZL 114 and mixed cryoglobulinemia. 115 The 5-year PFS and OS rates for patients treated with upfront antiviral therapy were 78% and 92%, respectively, and anti-HCV therapy at any time was independently associated with better OS. In addition, the outcome seems to be significantly better when pegylated IFN is used.…”
Section: Local Treatmentsmentioning
confidence: 89%
“…Antiviral therapy is successfully used in different non‐Hodgkin lymphoma subtypes but is more frequently being applied in MZLs. Treatment with pegylated IFN, with or without ribavirin, results in remission rates of 75% in patients with MZL and mixed cryoglobulinemia . The 5‐year PFS and OS rates for patients treated with upfront antiviral therapy were 78% and 92%, respectively, and anti‐HCV therapy at any time was independently associated with better OS.…”
Section: Treatmentmentioning
confidence: 99%
“…Рибавирин является аналогом гуанозина, предотвращающего синтез РНК HCV путем ингибирования РНК-полимеразы. При лечении взрослых он вызывает СВО у 50% пациентов с генотипом 1 и у 80% больных с генотипами 2 и 3 [44,52,54].…”
Section: современный взгляд на терапию хронического гепатита с у детей: прошлое настоящее перспективы будущегоunclassified
“…В крупных педиатрических исследованиях продемонстрировано [44], что комбинированная терапия пегилированным ИФН α и рибавирином приводит к СВО более чем у 1/2 больных с генотипами 1, 4, 5 и 6, и более чем у 90% пациентов с генотипами 2 и 3 [52,54,55].…”
Section: современный взгляд на терапию хронического гепатита с у детей: прошлое настоящее перспективы будущегоunclassified
“…A multitude of studies have demonstrated that genotype 1‐infected treatment‐naïve patients with LVL at baseline who achieve RVR can be treated with 24 weeks of PEG/RBV therapy without compromising SVR rates . Based on one of these trials, the European Medicines Agency (EMA) has approved the use of 24 weeks of PEG/RBV in genotype 1‐infected patients with low baseline viral loads (<600,000 IU/mL) who achieve RVR …”
mentioning
confidence: 99%